Another way to dance - Southgate, Martha (New York : Delacorte Press, 1996)
While spending the summer at the School of American Ballet in New York City, fourteen-year-old Vicki Harris must come to terms with the reality of her parents' divorce, her crush on Mikhail Baryshnikov, and the impact of being an African American on her future as a dancer.
Keywords: African Americans -- Fiction; Ballet dancing -- Fiction; Divorce -- Fiction; New York (N.Y.) -- Fiction